1956
DOI: 10.1084/jem.103.2.225
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the O Antigen of Salmonella Typhosa

Abstract: Investigations of factors affecting the immunological state of the host constitute a voluminous literature, most of which has been reviewed in a comprehensive treatise by Perla and Marmorston (1). However, of the great array of substances investigated, only a few have proved to be of consequence in that they provided new and productive approaches to improvement in the antibody response of the host.The contributions of major importance in this respect are: (a) the observations of Ramon (2) and of Glenn}" et al.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

1958
1958
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 293 publications
(60 citation statements)
references
References 17 publications
2
58
0
Order By: Relevance
“…LPS has adjuvant activity for protein antigens and enhances antibody responses [35]. In this study both meningococcal LOS and lipid A used as adjuvants induced in mice significantly high titers of IgG2a (10-fold increase) and IgG2b and less IgG1 but not IgG3.…”
Section: Discussionmentioning
confidence: 67%
“…LPS has adjuvant activity for protein antigens and enhances antibody responses [35]. In this study both meningococcal LOS and lipid A used as adjuvants induced in mice significantly high titers of IgG2a (10-fold increase) and IgG2b and less IgG1 but not IgG3.…”
Section: Discussionmentioning
confidence: 67%
“…23,24 As mentioned earlier, understanding the structural and mechanistic bases of adjuvanticity and toxicity is pivotal in rationally developing novel adjuvants. The progression from Johnson's experiments in 1956, 12 demonstrating the adjuvanticity of highly (PGN), a super-sized polymer of β-1→4-linked N-acetylglucosamine-N-acetylmuramic acid glycan strands that are cross-linked by short peptides. 70 Unlike in Gram-negative bacteria which bear LPS on the outer leaflet of the outer membrane, the external surface of the peptidoglycan layer is decorated with lipoteichoic acids (LTA; Fig.…”
Section: Tlr4 Agonists-lipopolysaccharide Monophosphoryl Lipid a Andmentioning
confidence: 99%
“…[7][8][9] In 1962, Dresser observed that injection of purified soluble proteins not only failed to stimulate an immune response, but tolerized animals unless a bacterial extract was admixed with the protein immunogen. 10 This led him to redefine adjuvanticity as "a property of a substance which can act as a physiological switch, directing at least some immunologically competent cells to respond by making antibody rather than by becoming immunologically paralyzed by the antigen," 11 confirming Johnson's earlier observations that lipopolysaccharide (LPS) from Gram-negative bacteria exerted potent adjuvant properties, 12 and perhaps paved the way for the subsequent discovery of the wide range of microorganism-derived adjuvants. 13 TLRs are pattern recognition receptors present on diverse cell types that recognize specific molecular patterns present in molecules that are broadly shared by pathogens but distinguishable from host molecules, collectively referred to as pathogen-associated molecular patterns (PAMPs).…”
mentioning
confidence: 94%
“…Now that it has been established, in several laboratories, that serum is capable of producing various types of alterations in endotoxins (15)(16)(17)(18)(19)(20)(21), it is important to learn about: (a) the nature of the components in serum which are responsible for these effects; (b) the mechanisms by which they bring about these changes; and (c) the changes produced in endotoxin itself. Further progress in these directions should be facilitated by distinguishing between those changes which are obtained only on protracted incubation (3 to 24 hours) and those which occur within a few minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work (15) had shown that endotoxins were capable of greatly enhancing the production of antibodies to proteins. However, no information was available as to whether an endotoxin can enhance production of antibody to a generically different endotoxin.…”
Section: Effect Of Heterologous Endotoxins On the Antigenicity Oj Typmentioning
confidence: 99%